Does repeated autoclave sterilization cause changes in the color and fragility of fiberglass reinforced resin crowns? - Ebru Delikan; Seçil Çaliskan; Ahmet Çalışkan; Canan Özdemir (BMC, 2023)
Abstract Background Since the effects of sterilization on the Fiberglass Reinforced Resin Crowns (FRRCs) is not well-known the aim of current study was to evaluate the effects of autoclave sterilization on the fracture resistance, color stability, and surface composition of FRRCs. Methods A total of 48 crowns were used. The crowns were divided into three groups according to the sterilization number: no sterilization (Control Group), one sterilization (Group 1), and four sterilizations (Group 2). The microstructure of the three crowns from each group was evaluated using scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX) spectroscopy. Thirteen FRRCs from each group were first used for color stability testing and then for the fracture resistance analysis. One-way analysis of variance (ANOVA), one-way repeated measures ANOVA, and paired t-tests were used in the statistical analysis. Results EDX results revealed that the weight% of surface silicon atoms in group 2 was significantly higher. Some crack lines could be observed on the SEM images. Statistically significant differences were found in color stability following the first and fourth sterilization cycles (p < .01). The increase in the sterilization cycle did not statistically decrease the fracture resistance of the FRRCs (p = .055); however, overall, a decreasing trend was observed in fracture resistance as the sterilization cycle increased. Conclusions Autoclave sterilization caused some changes in the surface elemental composition and surface morphology of FRRCs. Avoiding unnecessary FRRC trials is important to reduce the number of sterilizations.